Cyclic voltammetry and electrochemical impedance simulations of the mediator-type enzyme electrode reaction using finite element method. (20th January 2021) - Loew, Noya; Ofuji, Takashi; Shitanda, Isao; Hoshi, Yoshinao; Kitazumi, Yuki; Kano, Kenji; Itagaki, Masayuki
Abstract: Simulations enable fundamental electrochemistry to be more deeply understood and are useful tools for the further development of electrochemical processes. However, important parameter restrictions have thus far limited the applicability of electrochemical simulations. In this study, we developed a realistic model of mediator-type enzyme electrodes to accurately simulate cyclic voltammetry and electrochemical impedance spectroscopy by considering the current arising from electrochemical double-layer charging. Implementation of the finite element method in these calculations resulted in a model with very few boundary conditions. The model was successfully tested for various enzyme and electrode reaction kinetics and subsequently adapted to describe immobilized enzymes and mediators. The insight gained through this study has implications for the further development of biosensor and biofuel cell technologies.